Tensile properties and strengthening effects of Al 3003 alloy weldment reinforced with TiO2 nanoparticles. (15th October 2019) - Ramkumar, K.R.; Natarajan, S.
Abstract: This paper examines the significance of strengthening mechanisms in the fabricated Al 3003 nanocomposite weldment using accumulative roll bonded (ARB) Al 1100 – TiO2 filler rod. The wt. % of titanium oxide (TiO2 ) content is varied as 0, 0.75, 1.5, 2.25 and 3 to the total weight of the weld zone. The weld possesses an ultimate tensile strength of 249 ± 04 MPa in 3% reinforced whereas 137 ± 04 MPa in unreinforced condition. The results obtained from the tensile test were cross checked with the characterization studies such as X ray line profile analysis (XRD), Field emission scanning electron microscopic analysis (FESEM), Transmission electron microscopic analysis (TEM), Electron backscattered diffraction analysis (EBSD) and Energy dispersive x-ray spectroscopic analysis (EDS). The tensile test results reveal that Al – 3 wt% TiO2 nanocomposite weld exhibits higher strength which is not only due to drop in grain size but also due to mechanisms such as grain refinement strengthening, Orowan strengthening and thermal expansion coefficient mismatch strengthening and occurred incommensurate with the progressive addition of TiO2 nanoparticles in the weldment. However, it has been found that the mechanism due to Orowan strengthening has played a significant and greater role for the overall strength of the weldment.